2015
DOI: 10.1017/s002237781500121x
|View full text |Cite
|
Sign up to set email alerts
|

Quasilinear perturbed equilibria of resistively unstable current carrying plasma

Abstract: A formalism for consideration of island formation is presented using a model of a cylindrical resistively unstable plasma. Both current and pressure driven island formation at resonant surfaces are considered. The proposed formalism of perturbed equilibria avoids problems typical for linear analysis of resistive magneto-hydrodynamic instabilities related to extraction of the so-called small solution near the resonant surfaces. The matching technique of this paper is not sensitive to configuration parameters ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…, driving the tearing instability [21]. Here, ψ s − , ψ s + and ψ s are the radial gradient of the perturbed magnetic flux at both sides of the resonant surface and the value of the perturbed flux at the resonant surface, respectively.…”
Section: Mhd Response Caused By the Spimentioning
confidence: 99%
“…, driving the tearing instability [21]. Here, ψ s − , ψ s + and ψ s are the radial gradient of the perturbed magnetic flux at both sides of the resonant surface and the value of the perturbed flux at the resonant surface, respectively.…”
Section: Mhd Response Caused By the Spimentioning
confidence: 99%
“…For oblique modes, there is a logarithmic singularity in the derivative of the ideal solution since F /F is singular near the resonant surface 25,30 . However, the contribution of this logarithmic singularity to ψ is even in parity near the resonant surface, thus does not contribute to ∆ .…”
Section: A Effective Damping Caused By Linearly Stable Modesmentioning
confidence: 99%
“…The justification of using the linear growth rate to estimate effective damping may be formulated more precisely as follows. The effective island width w for a given Fourier component of the magnetic perturbation Bk (x, y, z) = B(0) k (x) exp (ik y y − ik z z) has the following dependence on mode numbers and the magnetic perturbation strength: 24,25 w…”
Section: A Effective Damping Caused By Linearly Stable Modesmentioning
confidence: 99%
“…While expensive 3D nonlinear MHD codes could be arranged to explore the aforementioned stability impact from profile modifications caused by either the DAS and the DMS, quasi-linear stability analysis using helical Grad-Shafranov equation [36] provides a more agile and cost-effective tool. In our simulation environment, which was run on a virtual machine on AMD R9 5900HX CPU, the typical convergence time ranges from 50 ms to 300 ms, depending on the strength of profile modification.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of this approach is its capability of avoiding the singularity in solutions close to the resonant surface, and accurately describing the impact of profile modification within the island on the stability criterion ∆ . [36] Considering a dominant finite sized island in a cylindrical analogue of the tokamak plasma with a toroidal effect multiplier 1 − m 2 /n 2 , [39] the 2D temperature and pressure profile modification with helical symmetry are described and their impact on the island stability is obtained through the calculation of ∆ up to the resonant surface. Several different combinations of the current density and pressure gradient modification are considered, and it is found that positive helical current perturbation on island O-point is always strongly stabilizing while the negative one does the opposite, consistent with previous analytical [40] and numerical results.…”
Section: Introductionmentioning
confidence: 99%